Pengaruh Karakteristik Perusahaan Terhadap Financial Distress Pada Perusahaan Manufaktur Sub Sektor Industri Barang Konsumsi Di BEI - Juang, Sari Enovani; Azis, Azolla Degita; Prasetia, Angga (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
Financial distress is a situation where a company experiences consecutive financial declines over several years which can lead to bankruptcy. Financial distress usually results from the failure of an entity to repay its debtors because it does not have sufficient funds to continue its operations. This research aims to determine the effect of leverage and company size on financial distress in manufacturing companies in the consumer goods industry sub-sector listed on the IDX for the 2019-2022 period. Where the leverage variable uses the Debt to equity ratio (DER) formula, the company size variable uses the LN Total Assets formula and the financial distress variable uses the Springate Scores (S-Scrores) formula. This type of research is quantitative with a sampling method based on purposive sampling, obtaining 33 companies which were used as research samples multiplied over 4 years for a total of 132 research data. By using secondary data obtained from the official IDX website during the research period. And processed using the SPSS version 26 program. The results of this research show that leverage has a negative effect on financial distress and company size has no effect on financial distress